If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x + 3) + (11x + -7) + (6x + 18) = 0 Reorder the terms: (3 + 9x) + (11x + -7) + (6x + 18) = 0 Remove parenthesis around (3 + 9x) 3 + 9x + (11x + -7) + (6x + 18) = 0 Reorder the terms: 3 + 9x + (-7 + 11x) + (6x + 18) = 0 Remove parenthesis around (-7 + 11x) 3 + 9x + -7 + 11x + (6x + 18) = 0 Reorder the terms: 3 + 9x + -7 + 11x + (18 + 6x) = 0 Remove parenthesis around (18 + 6x) 3 + 9x + -7 + 11x + 18 + 6x = 0 Reorder the terms: 3 + -7 + 18 + 9x + 11x + 6x = 0 Combine like terms: 3 + -7 = -4 -4 + 18 + 9x + 11x + 6x = 0 Combine like terms: -4 + 18 = 14 14 + 9x + 11x + 6x = 0 Combine like terms: 9x + 11x = 20x 14 + 20x + 6x = 0 Combine like terms: 20x + 6x = 26x 14 + 26x = 0 Solving 14 + 26x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 26x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 26x = 0 + -14 26x = 0 + -14 Combine like terms: 0 + -14 = -14 26x = -14 Divide each side by '26'. x = -0.5384615385 Simplifying x = -0.5384615385
| 7(-9x)=12 | | 5x-8y=-32 | | -5t^2+30t-15=30 | | 0.5=19.5 | | -6x+5y=-3 | | -9(x-3)-(8x-5)=-18x | | 5x+12-6x=5x-48 | | va-w=3 | | zx-w=3 | | 3y^2+5=50 | | 7-6(x+4)=-8 | | -9(m-2)-6(8m-9)=-58(m-1)-1 | | vx-w=3 | | 8x-2=-24x+10 | | Y^2+4=20 | | t+9=-2t-3-3t | | x-2=2x-14 | | 8x+3=5x+15 | | i=500*0.12*2 | | t+9=2t-3-3t | | -2+12=5 | | -8(1-5v)=31 | | -4(x-5)+3(-6x-6)=-23(x+1)-2 | | 4y^2+15y+2=0 | | p=2*3+2*136 | | 5(2a+4b)-9(a+7b)=0 | | x-1+40+70=180 | | 3(8c-1)-2=22c+3 | | 5(2x-2)-7=23 | | 78+6x=6(7x-5) | | 3-2x=3+1x | | 3(x+15)=15+3x |